1966
DOI: 10.1021/bi00876a004
|View full text |Cite
|
Sign up to set email alerts
|

The Peptide Subunit N α-(L-Alanyl-D-isoglutaminyl)-L-lysyl -D-alanine in Cell Wall Peptidoglycans of Staphylococcus aureus Strain Copenhagen, Micrococcus roseus R 27, and Sreptococcus pyogenes Group A, Type 14

Abstract: Gly°The following abbreviations are also used: N" for the -lysine derivatives on peptides; Ne for the on peptides. b Descending paper chromatography in solvent VI.e-lysine derivatives 1964). In contrast to the precursor peptide, however, the carbohydrate-free peptide isolated from S. aureus cell walls had only 1 mole of D-alanine, and in addition contained 1 mole of NHS. An Edman degradation carried out on this isolated peptide demonstrated that this ammonia was a substituent of the -carboxyl group of the glut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

1968
1968
2007
2007

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 26 publications
2
41
0
Order By: Relevance
“…2) reacted weakly with anti-N-acetylglucosamine antibody. These findings suggest the presence of a region of the streptococcal cell wall with a high degree of cross-linking (25,26) that is resistant to muralytic enzyme, thus trapping a portion of the M molecule within this resistant core. In Bacillus subtilis, an enzyme-resistant fraction of the cell wall has been described (6) and attributed to the cell wall ends, which are older and thus are likely to be more cross-linked.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…2) reacted weakly with anti-N-acetylglucosamine antibody. These findings suggest the presence of a region of the streptococcal cell wall with a high degree of cross-linking (25,26) that is resistant to muralytic enzyme, thus trapping a portion of the M molecule within this resistant core. In Bacillus subtilis, an enzyme-resistant fraction of the cell wall has been described (6) and attributed to the cell wall ends, which are older and thus are likely to be more cross-linked.…”
Section: Discussionmentioning
confidence: 91%
“…Evidence peptidoglycan is L-Ala-L-Ala (13), the absence of additional alanines from the amino acid composition of the wall-associated fragment (Table 1), which would be contributed by the peptide portion of the peptidoglycan, rules out any linkage through this moiety. Thus, although previous studies suggested a covalent interaction between the M protein and the cell wall (11), it is likely that the C-terminal region of the M protein is not covalently linked to but is intercalated within the highly cross-linked peptidoglycan (25). The nearly regular placement of prolines and glycines within this region suggests that some sort of specific structure may be necessary for this interaction (12).…”
Section: Discussionmentioning
confidence: 96%
“…Penicillin binding proteins polymerize peptidoglycan precursors into linear glycan strands that are cross-linked with neighboring strands, thereby generating a single large murein macromolecule (23,46,53). Staphylococcus aureus peptidoglycan is composed of N-acetylmuramoyl-(L-Ala-D-iGln-L-Lys(Gly 5 )-D-Ala)-(␤1-4)-N-acetylglucosamine (7,13,14,32). Polymerization of repeating disaccharide units, N-acetylmuramoyl-(␤1-4)-N-acetylglucosamine (MurNAc-GlcNAc), generates the glycan strands (3,8).…”
mentioning
confidence: 99%
“…Penicillin-binding proteins (PBPs), another group of bacterial transpeptidases, cleave cell-wall peptides at the amide bond of D-Ala-D-Ala (16,17). The carboxyl group of the cleaved peptide is ester-linked to the hydroxyl group of the active-site serine residue (18,19).…”
mentioning
confidence: 99%